Analisis Pemanfaatan Bank Sampah Untuk Meningkatkan Nilai Jual Dan Nilai Tambah Pada Masyarakat Dengan Pendekatan Sircular Economy (3R) Di Kota Medan Ditinjau Dalam Konsep Ekonomi Islam - Shyella Putri Mandasari; Sri Ramadhani; Mawaddah Irham (Ekonomi Bisnis Manajemen dan Akuntansi (EBMA), 2025)
Currently the use of waste banks with a circular economy (3R) approach provides recycling-based business opportunities to increase employment opportunities, investment, economic growth and increase regional income. The purpose of this research is to find out the potential added value of waste bank management using circular economy (3R) and to find out the benefits and constraints of the Anyelir Ampah Bank and the New Normal Main Garbage Bank and to find out economic added value in the concept of Islamic economics. This research method uses descriptive qualitative research. The research data used are primary and secondary data obtained from the Carnation Garbage Bank and the New Normal Main Garbage Bank. Data collection techniques used observation, interviews and documentation and data analysis techniques were carried out by collecting data, data reduction, data presentation and drawing conclusions. The results of this study indicate that the added economic value of waste bank management with a circular economy (3R) is still low, public awareness in managing waste is still very concerning, limited manpower to socialize about the waste bank program to the community is still not optimal, and marketing handicraft products still simple. The benefits that can be felt by managing a waste bank are financial ability and a clean environment. the benefits obtained are from an environmental perspective, namely the environment will be clean, from an economic perspective, it can increase income a little, from an educational perspective, it can provide knowledge to the whole community about the importance of saving waste, from a government perspective, it can help reduce landfill waste in the city of Medan. . The obstacles in the Carnation Garbage Bank and the New Normal Waste Bank range from operational costs, inadequate land and production equipment, to education and outreach efforts to the community. The added value in the concept of Islamic economics with waste management is the added value of the waste management process which according to Islam is permissible and lawful.